Predicting speech-in-speech recognition: Short-term audibility and spatial separation - Wasiuk, P.A.; Calandruccio, L.; Oleson, J.J.; Buss, E. (Journal of the Acoustical Society of America, 2023)
Quantifying the factors that predict variability in speech-in-speech recognition represents a fundamental challenge in auditory science. Stimulus factors associated with energetic and informational masking (IM) modulate variability in speech-in-speech recognition, but energetic effects can be difficult to estimate in spectro-temporally dynamic speech maskers. The current experiment characterized the effects of short-term audibility and differences in target and masker location (or perceived location) on the horizontal plane for sentence recognition in two-talker speech. Thirty young adults with normal hearing (NH) participated. Speech reception thresholds and keyword recognition at a fixed signal-to-noise ratio (SNR) were measured in each spatial condition. Short-term audibility for each keyword was quantified using a glimpsing model. Results revealed that speech-in-speech recognition depended on the proportion of audible glimpses available in the target + masker keyword stimulus in each spatial condition, even across stimuli presented at a fixed global SNR. Short-term audibility requirements were greater for colocated than spatially separated speech-in-speech recognition, and keyword recognition improved more rapidly as a function of increases in target audibility with spatial separation. Results indicate that spatial cues enhance glimpsing efficiency in competing speech for young adults with NH and provide a quantitative framework for estimating IM for speech-in-speech recognition in different spatial configurations. © 2023 Acoustical Society of America.
0 citations (Crossref) [2023-10-31]
Keywords: dept.cmd; peer-reviewed